Imbalance between endothelial damage and repair capacity in chronic obstructive pulmonary disease. - Jéssica García-Lucio; Victor I Peinado; Lluís de Jover; Roberto Del Pozo; Isabel Blanco; Cristina Bonjoch; Núria Coll-Bonfill; Tanja Paul; Olga Tura-Ceide; Joan Albert Barberà (PLoS ONE, 2018)
Circulating endothelial microparticles (EMPs) and progenitor cells (PCs) are biological markers of endothelial function and endogenous repair capacity. The study was aimed to investigate whether COPD patients have an imbalance between EMPs to PCs compared to controls and to evaluate the effect of cigarette smoke on these circulating markers.Circulating EMPs and PCs were determined by flow cytometry in 27 nonsmokers, 20 smokers and 61 COPD patients with moderate to severe airflow obstruction. We compared total EMPs (CD31+CD42b-), apoptotic if they co-expressed Annexin-V+ or activated if they co-expressed CD62E+, circulating PCs (CD34+CD133+CD45+) and the EMPs/PCs ratio between groups.COPD patients presented increased levels of total and apoptotic circulating EMPs, and an increased EMPs/PCs ratio, compared with nonsmokers. Women had less circulating PCs than men through all groups and those with COPD showed lower levels of PCs than both control groups. In smokers, circulating EMPs and PCs did not differ from nonsmokers, being the EMPs/PCs ratio in an intermediate position between COPD and nonsmokers.We conclude that COPD patients present an imbalance between endothelial damage and repair capacity that might explain the frequent concurrence of cardiovascular disorders. Factors related to the disease itself and gender, rather than cigarette smoking, may account for this imbalance.